Implications of Economic Incentivization of User-Generated Content on Local Film and Television Production in Kenya - Mulinya, Sheila; Ndavula, John; Mutua, Joan (International Journal of Communication and Public Relation, 2025)
Purpose: The aim of the study was to explore how economic incentivization through social media influence, endorsements and brand ambassadorship drives UGC as a disruptive force in local film and TV production in Kenya. It also examined how these incentives challenge traditional/legacy media norms are reshaping audio-visual content creation and distribution. Methodology: The study employed a descriptive mixed-methods design that integrated both quantitative and qualitative approaches to examine the influence of economic incentivization on UGC in local film and TV production in Kenya. For the quantitative component, data was collected through structured questionnaires from a sample of 384 respondents, who were selected using a proportionate stratified random sampling technique. The target population comprised 2,716 local film and TV producers, as well as UGC creators on YouTube, Instagram, and TikTok. Stratified sampling ensured that respondents were selected proportionally from these different subgroups, allowing for a representative sample. The data was analyzed using descriptive statistics (percentages) and inferential statistical methods (correlation, regression and ANOVA), through SPSS (Version 25). The results were presented in pie charts, graphs and tables. For the qualitative component, in-depth interviews were conducted with 24 key informants drawn from the local film and TV production industry, Kenya Film Commission (KFC), Kenya Film Classification Board (KFCB), Kenya Copyright Board (KECOBO), Department of Film Services (DFS) and the Communications Authority of Kenya (CA). These key informants were selected using purposive sampling, which ensured that individuals with relevant expertise and industry knowledge provided valuable and expert insights for the study. Qualitative data was analyzed thematically to complement the quantitative findings. Findings: The study found that economic incentivization significantly influences the production of UGC and its effect on local film and TV production in Kenya. About 83.9% of respondents agreed that brand endorsements and ambassadorships provide meaningful rewards, enabling creators to produce relatable and culturally relevant content. Additionally, 79.9% acknowledged that brand ambassadors influence consumer purchasing decisions while 59.2% viewed social media influencing as an accessible opportunity. However, 22.3% of the respondents strongly agreed that existing monetization models were satisfactory but highlighted challenges in existing compensation structures. The findings demonstrate that economic incentives empower creators to improve content quality and audience engagement, reshaping local film and TV production in Kenya by challenging traditional/legacy media production financing models and norms. However, gaps in policy support and inconsistent funding remain present as barriers to maximizing the transformative potential of UGC. Unique Contribution to Theory, Practice and Policy: The findings of this study contribute to Disruptive Innovation Theory (DIT) by applying it to UGC within film and TV production, showing how economic incentives such as social media influence, endorsements and brand ambassadorships drive UGC as a disruptive force that challenges traditional media. It provides a framework for understanding how financial motivations democratize content creation, enabling independent content creators to effectively engage audiences. These insights will guide film and TV producers, advertisers as well as audio-visual content creators in leveraging UGC for sustainable growth while emphasizing the need for traditional/legacy media to adapt. The study also highlights the importance of supportive policies that can ensure that there is fair compensation while encouraging collaborations between traditional/legacy film and TV producers and online digital creators, advocating for a more inclusive and diversified local media content production industry that will recognize digital creators as essential stakeholders.